Borobudur: Human Heritage - Daoed Joesoef (Kompas Media Nusantara, 2016)
Thirteen centuries ago, a number of unknown artisan and priest constructed a structure from massive stones in an area considered to be secred in central java also surrounded by several volcanoes. this book describes the archeological, historical, spiritual, cultural, scientific,aesthetic, economic, and political values of chandi borobudur and also the mystery of the unfinished buddha